Flow-induced errors in airborne in situ measurements of aerosols and clouds - A. Spanu; M. Dollner; J. Gasteiger; T. P. Bui; B. Weinzierl (Atmospheric Measurement Techniques, 2020)
Aerosols and clouds affect atmospheric radiative processes and climate in many complex ways and still pose the largest uncertainty in current estimates of the Earth's changing energy budget. Airborne in situ sensors such as the Cloud, Aerosol, and Precipitation Spectrometer (CAPS) or other optical spectrometers and optical array probes provide detailed information about the horizontal and vertical distribution of aerosol and cloud properties. However, flow distortions occurring at the location where these instruments are mounted on the outside of an aircraft may directly produce artifacts in detected particle number concentration and also cause droplet deformation and/or breakup during the measurement process. Several studies have investigated flow-induced errors assuming that air is incompressible. However, for fast-flying aircraft, the impact of air compressibility is no longer negligible. In this study, we combine airborne data with numerical simulations to investigate the flow around wing-mounted instruments and the induced errors for different realistic flight conditions. A correction scheme for deriving particle number concentrations from in situ aerosol and cloud probes is proposed, and a new formula is provided for deriving the droplet volume from images taken by optical array probes. Shape distortions of liquid droplets can either be caused by errors in the speed with which the images are recorded or by aerodynamic forces acting at the droplet surface caused by changes of the airflow when it approaches the instrument. These forces can lead to the dynamic breakup of droplets causing artifacts in particle number concentration and size. An estimation of the critical breakup diameter as a function of flight conditions is provided. Experimental data show that the flow speed at the instrument location is smaller than the ambient flow speed. Our simulations confirm the observed difference and reveal a size-dependent impact on particle speed and concentration. This leads, on average, to a 25 % overestimation of the number concentration of particles with diameters larger than 10 µm diameter and causes distorted images of droplets and ice crystals if the flow values recorded at the instrument are used. With the proposed corrections, errors of particle number concentration and droplet volume, as well as image distortions, are significantly reduced by up to 1 order of magnitude. Although the presented correction scheme is derived for the DLR Falcon research aircraft (Saharan Aerosol Long-range Transport and Aerosol-Cloud-Interaction Experiment (SALTRACE) campaign) and validated for the DLR Falcon (Absorbing aerosol layers in a changing climate: aging, lifetime and dynamics mission conducted in 2017 (A-LIFE) campaign) and the NASA DC-8 (Atmospheric Tomography Mission (ATom) campaigns), the general conclusions hold for any fast-flying research aircraft.